Produksi Video Profile Sebagai Sebagai Bentuk Promosi Program Studi Penyiaran Berbasis Multimedia - Supriyadi Sandi; Ade Christian (Jurnal Media Penyiaran, 2021)
Video profile is a communication media industry in the form of video which is intended to present information, data, and promotion of something to the general public. With profile videos, the public, both prospective clients and prospective consumers, can find information. Not only that, it can build a company's image or image. The public can understand, take into account and remember the companies that broadcast in the form of a video profile. In the video profile will be shown from the vision and mission, the direction of policies, the company's strategic steps that will be carried out. The work culture and management system in the company can be seen in the impressions that are formed in a video profile so that the public can find out the shape of the company. The UBSI Broadcasting Study Program in developing and promoting the study program tries to provide information and an overview of multimedia technology in the form of making a video profile. The making of the broadcasting video profile was made by utilizing the expertise and knowledge of the staff involved in the making. The video profile produces quality videos in delivering messages that are right on target at this time. The research method used is Literature, Observation, Interview, Design and Implementation, and Documentation. The work steps in the production stage consist of Pre-Production, Production and Post-Production processes. The implementation of this video production is expected to be a reference and information in introducing the broadcasting study program from Bina Sarana Informatika University